The Effect of E-Learning Program for COVID-19 Patient Care on the Knowledge of Nursing Students: A Quasi-Experimental Study - Sorour Khari MSc; Marzieh Pazokian PhD; Atefe Salimi Akin Abadi MSc; Mina Zarmehrparirouy MSc; Yones Ahmadvand MSc (SAGE Publishing, 2022)
Introduction As COVID-19 is an emerging disease, nursing students have little experience in caring for COVID-19 patients while they will be part of the country's health system and have the closest relationship with the treatment team. Objective(s) Therefore, considering the importance and challenges of nursing students' education during the COVID-19 pandemic, the present study aimed to investigate the effect of e-learning programs for COVID-19 patient care on nursing students' knowledge in Tehran, Iran 2021. Methods The present quasi-experimental study was performed on 100 nursing students selected by a random sampling method. The demographic and knowledge assessment questionnaires were used to collect data before the intervention. Then, the e-learning program was implemented, in which students participated in three sessions for two weeks, the educational content was provided for the students in the form of text, audio, video, and image files, and questions were asked to them. Data were collected immediately after completing the e-learning program and four weeks later. Results The mean age value was 22 ± 1.25, and 61% of participants were female. The total mean score of knowledge immediately after training (22.95 ± 0.30) and one month after training (22.79 ± 0.30) significantly increased compared to baseline time (17.21 ± 0.48). The main effect of time was significant for the total score of knowledge from baseline to immediately after training (B = 5.79) and one-month follow-up (B = 5.63). Conclusion The findings of the study showed that the total mean score of the knowledge of students increased significantly in all dimensions after the e-learning program for COVID-19 patient care. Implications for nursing practice Considering the effectiveness of the e-learning program for COVID-19 patient care in increasing the knowledge of nursing students, it is necessary to provide more training programs focusing on new scientific findings because increasing nurses' and nursing students' knowledge plays a significant role in achieving more skills and promoting community health.